Diffusion of Geo-Environmental datasets through online interactive and real-time applications. Case study: the Natura GR2440006 protected area - Antoniou, V.; Vassilakis, E (Annals of Geographical Studies, 2019)
A web - interactive application which spreads geo-environmental information over the internet and also accepts and manages real time rural data is described in this paper. Story Maps context has been chosen for this reason, since this is considered to be a new and innovative Web-based Geographic Information System application method for using it as a mean for organizing and presenting new digital geographic information by combining interactive maps with multimedia and other apps simultaneously in one platform. The protected area of Kallidromo Mt. (central Greece) was chosen as a case study, due to its environmental sensitivity since it is characterized as Natura protected area and also because of the availability of several kinds of geospatial data.